O habeas corpus para além da espécie humana - Rollo, Sandro Cavalcanti (2016)
In the last ten years some writs of habeas corpus have been filed, in Brazil and in other countries, on behalf of great primates. It is a matter of constitutional order and one more instrument utilized for activists for the recognition of the Animal s Rights. This slope, even if generates many controversies, is coming neatly bigger in the past few years, as we can verify throughout the doctrinal and jurisprudential production. The sentience always have been the central element inside the debates evolving the rela-tionship between humans and other animals. Scientific progress that have finding the impressive genetic closeness among us and the great primates, boosted the requests of habeas corpus on behalf of the latter. The grant of the order and, consequently, the admission of rights to the animals generates countless questionings. If the humankind proceeds in the path of the emancipatory trajectory and after receiving all human be-ings in their moral community, could receive , what seems to be the last frontier, the animals, many questionings should be subject of analysis, that already derives from the own grant of the writ to the anthropoids. So, what animals, which rights, what cri-teria to concede them, what judicial instruments must be used to protect them, what is the consequence for humans of the acknowledgment of the Animals Rights and what criteria should be utilized in a conflict of interests between human animals and nonhu-man animals, are some of the largely complex questionings that will be subject of re-flection in the present work